2020
DOI: 10.1186/s13041-020-00569-6
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine inhibits amyloid beta-induced astrocyte activation and protects neurons against indirect toxicity

Abstract: Amyloid beta is a major constituent of the plaques found in the brains of patients suffering from Alzheimer's disease (AD). A growing body of research work suggests that neuroinflammation plays important roles in the development of AD. Thus, considerable efforts are directed towards identification of compounds that can reduce or inhibit neuroinflammation. Here, we show that sinomenine, a compound present in a Chinese medicinal plant, Sinomenium acutum, inhibits oligomeric amyloid beta-induced production of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Astrocytes are key elements in maintaining homeostasis and regulators of multiple physiological functions in brain [71]. However, they are responsive to various stimuli, and astrocyte dysfunction may impair neuronal function and thus lead to neurodegeneration [72]. Many studies showed that activated astrocytes are a common neuropathological feature of brain disorders that respond to Aβ metabolically, morphologically, and/or functionally [73].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are key elements in maintaining homeostasis and regulators of multiple physiological functions in brain [71]. However, they are responsive to various stimuli, and astrocyte dysfunction may impair neuronal function and thus lead to neurodegeneration [72]. Many studies showed that activated astrocytes are a common neuropathological feature of brain disorders that respond to Aβ metabolically, morphologically, and/or functionally [73].…”
Section: Discussionmentioning
confidence: 99%
“…In China, Sinomenine is a recommended medicine for the patient against rheumatoid arthritis. It has shown neuroprotection against Aβ-induced glial-mediated toxicity to neurons [ 150 , 151 ]. The mechanism of Sinomenine is not clearly understood.…”
Section: Therapeutic Approaches To Combat Neuroinflammation In Admentioning
confidence: 99%
“…Astrocytes have been shown to surround these plaques ( Olabarria et al, 2010 ; Perez-Nievas and Serrano-Pozo, 2018 ) and ingest Aβ molecules ( Jones et al, 2013 ; Söllvander et al, 2016 ). Exposure to aggregated Aβ induces reactive astrogliosis and increases astrocytic production of inflammatory mediators ( Singh et al, 2020 ), while ingestion of aggregated Aβ can impair lysosome function, hinder astrocytic degradation of Aβ protofibrils and alter the cargo of ADEVs ( Söllvander et al, 2016 ).…”
Section: Dysregulation Of Microrna and Their Target Mrna In Astrocyte...mentioning
confidence: 99%